The socialism of fools? : leftist origins of modern anti-semitism - Brustein, William 1947- (Cambridge Univ. Press, 2015)
"Anti-Semitism, as it has existed historically in Europe, is generally thought of as having been a phenomenon of the political right. To the extent that nineteenth- and early twentieth-century leftist movements have been found to manifest anti-Semitism, their involvement has often been suggested to be a mere fleeting and insignificant phenomenon. As such, this study seeks to examine more fully the role that the historic European left has played in developing and espousing anti-Semitic views. The authors draw upon a range of primary and secondary sources, including the analysis of left- and right-wing newspaper reportage, to trace the relationship between the political left and anti-Semitism in France, Germany, and Great Britain from the French Revolution to World War II, ultimately concluding that the relationship between the left and anti-Semitism has been much more profound than previously believed"..